Prototype Sistem Informasi Publik dan Prediksi Produksi Karet Menggunakan Metode Naive Bayes Berbasis Website - Wulandari, Cindi; Rizki, Fido; Lestari, Ayu (BEES: Bulletin of Electrical and Electronics Engineering, 2022)
The problem in this research is currently, public information to every village community is not carried out effectively because public information is carried out directly so that people who want to know village information must come directly to the Ngestiboga Village office 1. For the process of serving the letters needed by the community through a long process. The community must take care of, for example, a cover letter from the head of the hamlet and then forward it to the Ngestiboga 1 Village Office, where to carry out the service process to take care of the letters is difficult for the community because it is a long process. This study used data collection methods by conducting observations in Ngestiboga 1 Village, Jayaloka District, interviews with staff or the head of Ngestiboga 1 Village, Jayaloka District and literature on books related to the author's title, The results of the research are Public Information System Design and Rubber Production Prediction, the application is built using the PHP programming language with MYSQL as the application database and the application interface is built based on a Website and nave Bayes will be used as an algorithm for rubher production prediction. It can be concluded that the system can provide information and public services online to the community of Ngestiboga I Village, Jayaloka District and apply the Naive Bayes Algorithm so as to produce information on rubber production in the future.